2018
DOI: 10.1186/s13028-018-0384-6
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein, glucose and iron concentrations are significantly altered in dogs undergoing open ovariohysterectomy or ovariectomy

Abstract: BackgroundThere are relatively few studies about the canine surgical stress response, a sequence of events orchestrated by the body in response to a surgical trauma which is sometimes, as shown in human surgery, deleterious to the patient. There is a need to identify objective markers to quantify this response in order to estimate tissue trauma and use the markers as potential early indicators of surgical complications. The study objective was to investigate the surgical stress response, measured by C-reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
(78 reference statements)
1
15
0
Order By: Relevance
“…All dogs displayed a significant increase in CRP 18 h after surgery. These results are consistent with previous studies reporting an increase in CRP within the first 24 h after OHE with a subsequent reduction in the absence of ongoing trauma (32)(33)(34)(35)(36). HBOT has been shown, previously, to reduce CRP concentration in people with traumatic brain injury treated with 4 hyperbaric oxygen treatments at 3-day intervals (1 h on 100% oxygen at 2.0 ATA) (5), and in children with autism after 40 hyperbaric oxygen treatments at 1-to 2-day intervals (45 min on 100% oxygen at 1.3 and 1.5 ATA) (37).…”
Section: Discussionsupporting
confidence: 93%
“…All dogs displayed a significant increase in CRP 18 h after surgery. These results are consistent with previous studies reporting an increase in CRP within the first 24 h after OHE with a subsequent reduction in the absence of ongoing trauma (32)(33)(34)(35)(36). HBOT has been shown, previously, to reduce CRP concentration in people with traumatic brain injury treated with 4 hyperbaric oxygen treatments at 3-day intervals (1 h on 100% oxygen at 2.0 ATA) (5), and in children with autism after 40 hyperbaric oxygen treatments at 1-to 2-day intervals (45 min on 100% oxygen at 1.3 and 1.5 ATA) (37).…”
Section: Discussionsupporting
confidence: 93%
“…High CRP indicates either acute phase response or local wound problems. Moldal et al (2018) reported that OHE and OVE induce a surgical stress response with postoperative increases in glucose concentration and CRP, but not signifcant diference between the OHE and OVE. Dabrowski et al (2009) mentioned that the difficulties in postoperative wound healing were induced by infection with Escherichia coli and Staphylococcus spp., leading to re-increased levels of CRP and SAA immediately after surgery and persistently higher levels throughout the experiment.…”
Section: Introductionmentioning
confidence: 94%
“…Described techniques for bitch surgical sterilization are ovariectomy (OVE) and ovariohysterectomy (OVH), being both equally effective. OVE has potential advantages as smaller incisions, better viewing of the ovarian vessels and lower risk of surgical complications [26][27][28][29][30]. However, this technique should not be used if there is uterine disease or to prevent uterine neoplasm [26].…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory biomarkers have also been studied in conjunction with the leucogram to monitor the post-operative period in dogs [60,61], as well as after surgical trauma in other species such as cows [62,63]. Specific studies on APR after surgical neutering (OVE or OVH techniques) are described in both dogs and cats [11,16,28,58].…”
Section: Introductionmentioning
confidence: 99%